Identification of the epidermal growth factor receptor as the receptor for Salmonella Rck–dependent invasion. Issue 12 (8th September 2016) - Wiedemann, Agnés; Mijouin, Lily; Ayoub, Mohammed Akli; Barilleau, Emilie; Canepa, Sylvie; Teixeira‐Gomes, Ana Paula; Le Vern, Yves; Rosselin, Manon; Reiter, Eric; Velge, Philippe
ABSTRACT: The Salmonella Rck outer membrane protein binds to the cell surface, which leads to bacterial internalization via a Zipper mechanism. This invasion process requires induction of cellular signals, including phosphorylation of tyrosine proteins, and activation of c‐Src and PI3K, which arises as a result of an interaction with ahost cell surface receptor. Inthis study, epidermalgrowthfactor receptor (EGFR)was identified as thecell signaling receptor required for Rck‐mediated adhesion and internalization. First, Rck‐mediated adhesion and internalization were shown to be altered when EGFR expression and activity were modulated. Then, immuno precipitations were performed to demonstrate the Rck–EGFR interaction. Furthermore, surface plasmon resonance biosensor and homogeneous time‐resolved fluorescence technologies were used to demonstrate the direct interaction of Rck with the extracellular domain of human EGFR. Finally, our study strongly suggests a noncompetitive binding of Rck and EGF to EGFR. Overall, these results demonstrate that Rck is able to bind to EGFR and thereby establish a tight adherence to provide a signaling cascade, which leads to internalization of Rck‐expressing bacteria.—Wiedemann, A., Mijouin, L., Ayoub, M.A., Barilleau, E., Canepa, S., Teixeira‐Gomes, A. P., LeVern, Y., Rosselin, M., Reiter, E., Velge, P. Identification of the epidermal growth factor receptor as the receptor for Salmonella Rck–dependent invasion. FASEB J. 30, 4180–4191 (2016). www.fasebj.org